Prospectively shared control data across concurrent randomised clinical trials. (March 2023) - Kotecha, Gopal; Ventz, Steffen; Trippa, Lorenzo
Abstract: Sharing data from control groups across concurrent randomised clinical trials with identical enrolment criteria and the same control therapy can translate into efficiencies for the drug development process. We discuss potential benefits and risks of prospective data-sharing plans for concurrent randomised trials . Highlights: The current trial landscape consists of independent trials that do not share data. There is a need for trial designs to improve drug development efficiency. We propose sharing control arm data between concurrent randomised trials. This represents a sweet spot between existing approaches with limited risks of bias. Simulations based on data from glioblastoma confirm the benefits of this approach.